AGRO-PHYSIOLOGICAL CHARACTERIZATION OF DURUM WHEAT GENOTYPES UNDER DROUGHT CONDITIONS. (6th May 2018) - MOHAMMADI, REZA; ETMINAN, ALIREZA; SHOSHTARI, LIA
SUMMARY: Knowledge of agro-physiological traits associated with drought tolerance would be useful for developing breeding materials for drought-prone environments. This study was conducted (i) to estimate genetic variability among 25 durum wheat genotypes in response to drought based on grain yield and 15 agro-physiological traits in single and multi-year trials; and (ii) to compare genotypes on the basis of multiple investigated traits using genotype by trait (GT) biplot technique and then recommend possible selection strategies. We found large genetic differences among durum wheat genotypes for agro-physiological traits in response to drought stress within and between single years, which revealed good promise in their further exploitation for selection in durum wheat breeding program. High broad-sense heritability and expected genetic advance as percent of mean observed in plant height (90.8%; 52.7%), grain yield (53.6%, 23.5%) and relative water loss (47.2%, 41.3%), respectively, indicated a major role of additive gene action. The results showed that the performance of genotypes was influenced by the year. The traits with high consistence across years were heading date, plant height and peduncle length. The potential quantum efficiency of photosystem II (Fv/Fm) and thousand-kernel weight (TKW) were positively associated with grain yield, while heading date, plant height and canopy temperature (CT) were negatively associated with grain yield under the drought conditions. In conclusion, based on across-year analyses, Fv/Fm, TKW, heading date, plant height and CT are the most promising traits for indirect selection.